A dataset of behavioral measures on Chinese word production in picture naming - Chen Feng; Markus F. Damian; Qingqing Qu (Scientific Data, 2024)
Abstract Most studies of language production have been conducted with speakers of alphabetic languages, but relatively little research has examined languages with non-alphabetic scripts, such as Chinese. Moreover, most work on language word production has investigated phonological output processing (i.e., speaking), whereas comparatively little research has focused on orthographic output, such as writing and typing. Work on non-alphabetic languages and/or written production is particularly promising, given that it speaks to universalities vs. specificity in terms of architectures and mechanisms underlying language processing across all world languages and modalities. The current article reports a dataset of word production in Chinese with spoken and written responses, which includes reaction times of 193,851 trials of naming 403 pictures obtained from 667 participants across 23 Chinese word production experiments. All data were collected in the same experimental environment and from participants with relatively homogenous characteristics, using the same protocols and parameters. The dataset enables researchers to explore how Chinese speakers produce spoken and/or written words, and to identify language-specific features underlying word production.